SUBLINGUAL VITAMIN D3 DRUG THERAPY IN VITAMIN D DEFICIENCY PATIENTS AT PRAVARA RURAL HOSPITAL - Goud T, Sanjeeva Kumar; Kunkulol, Rahul (International Journal of Clinical and Biomedical Research, 2019)
The present study was aimed to study the effect of Sublingual Vitamin D3 on Serum Vitamin D level in Vitamin D deficiency patients. This was a cross-sectional and interventional study. All the Vitamin D deficiency patients of age 18-60years and either gender, willing to participate in the study were included. Patients who had greater than 20 ng/ml were excluded from the study. The total number of participants in our study was 200, out of these 111 males and 89 females, the mean age in our study was 51.07 ± 7.39Yrs. All volunteers were given sublingual vitamin D3 (60,000IU) in six doses every fifteen days of follow up for 3 months. The subject’s serum 25(OH)D levels were estimated before and after the treatment of sublingual vitamin D3. There was a statistically significant difference in serum vitamin D3 level before 16.61±6.71 ng/ml and after 35.80±7.80 ng/ml after treatment with Sublingual Vitamin D3. Six doses of 60,000IU of Vitamin D3 sublingual route having improved the role of serum 25(OH)D levels in the treatment of Vitamin D3 deficiency patients. Keywords: Vitamin D3; Sublingual route